Parent Communication Prompt to Increase Shared Decision-Making: A New Intervention Approach - Hubner, Lauren M.; Feldman, Heidi M.; Huffman, Lynne C. (Frontiers in Pediatrics, 2018)
Objective: Shared decision-making (SDM) is the process by which patients, clinicians, and in pediatrics, parents/caregivers, discuss treatment options, communicate available evidence for or against the different options, share preferences and values, and eventually arrive at a joint decision. This study evaluates the use of a novel, universally applicable, SDM intervention, provided to parents, intended to promote engagement and participation with their child’s clinician. Methods: 2-arm randomized controlled trial comparing the impact of a SDM-focused intervention prompt to a neutral comparison prompt on perception of SDM participation. Participants included English-speaking parents of children (0-17 years) attending one Developmental-Behavioral Pediatric (DBP) clinic and their child’s clinician. Prior to visit start, parents received either the intervention prompt encouraging engagement with the clinician in decision-making, or the comparison prompt reminding them to request a school/work excuse note if needed. After the visit, SDM was assessed by both parents and DBP clinicians. SDM was scored as present if the respondent answered “strongly agree” to all SDM-related items. Logistic regression tested effects of visit, child, parent, clinician characteristics, and intervention group status on parent-reported SDM. Cohen’s kappa assessed alignment between parent and clinician perceptions of SDM. Results: Of 88 parents screened, 50 (61%) met eligibility criteria and agreed to participate (intervention n=26; comparison n=24). Eligible participants (parents and clinicians) for analysis completed the surveys with no missing data. Overall, SDM was present in 76% of parents and 34% of clinicians. With high rates of parent-reported SDM in both intervention and comparison groups, no main intervention effect was detected. Compared to the comparison group, there was greater alignment between parent and clinician perception of SDM in the intervention group. Conclusions: Parent and clinician enrollment and data collection with minimal loss suggest that this novel approach is easy to use and could be employed in future outpatient studies exploring SDM. In this clinical setting, both intervention and comparison group parents reported high levels of SDM participation and no main group effect was detected. Further study of this novel parent-directed SDM intervention approach is needed in a larger sample with greater variability in parent-reported SDM to determine its efficacy.